2020
DOI: 10.1530/edm-20-0058
|View full text |Cite
|
Sign up to set email alerts
|

Should immunohistochemical expression of mismatch repair (MMR) proteins and microsatellite instability (MSI) analysis be routinely performed for poorly differentiated colorectal neuroendocrine carcinomas?

Abstract: Summary Colorectal poorly differentiated neuroendocrine carcinomas (NECs) are typically associated with poor outcomes. The mechanisms of their aggressiveness are still being investigated. Microsatellite instability (MSI) has recently been found in colorectal NECs showing aberrant methylation of the MLH1 gene and is associated with improved prognosis. We present a 76-year-old lady with an ascending colon tumour showing features of a pT3 N0 R0, large cell NEC (LCNEC) following right hemicolectomy. The adjacent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Currently, MSI and MMR protein deficiency have been explored in different malignancies, particularly to address an indication of ICPI [82][83][84][85][86][87][88]. Exploring the MMR/MSI status should become the new standard in poorly differentiated NEN, regardless of germline mutations consistent with LS [85][86][87][88].…”
Section: Nen and Mmr/msi Assessmentmentioning
confidence: 99%
“…Currently, MSI and MMR protein deficiency have been explored in different malignancies, particularly to address an indication of ICPI [82][83][84][85][86][87][88]. Exploring the MMR/MSI status should become the new standard in poorly differentiated NEN, regardless of germline mutations consistent with LS [85][86][87][88].…”
Section: Nen and Mmr/msi Assessmentmentioning
confidence: 99%
“…Colorectal NECs are morphologically similar to neuroendocrine carcinoma of the lung, and they can be large or small cell carcinomas. Small cell NECs arise from the squamous mucosa from the anal canal, and large cell NECs from the glandular mucosa of the large intestine [118]. Small cell NECs possess cells with minimal amounts of cytoplasm as well as granular nuclear chromatin, and these cells form ribbon-like structures.…”
Section: Histopathologymentioning
confidence: 99%
“…It was shown that early-stage MMR-deficient NECs have a better prognosis compared with MMR-proficient NECs. According to the Royal College of Pathologists in the United Kingdom, MMR protein expression status is a core data item of the histopathology report [118]. MicroRNAs are very promising markers in diag-nosing colorectal NENs.…”
Section: Diagnostic Work-upmentioning
confidence: 99%